Penanaman Pohon di Perumahan Bukit Permata Sumbari II Kecamatan Tenayan Raya, Pekanbaru - Hanifah Ikhsani; Azwin; Ambar Tri Ratnaningsih (Universitas Lancang Kuning, 2021)
Bukit Permata Sumbari II has a dry environment and Podsolik Merah Kuning soil type so that the people really need to improve the environmental conditions around the housing through tree planting activities. The problem of partners is the difficulty in getting tree seedlings, planting equipment to fertilizer. Team provided a solution by providing counseling the technical and maintenance of trees, also facilitated tree planting activities so that the residential environment was balanced. The activities carried out were counseling on tree planting and maintenance techniques, procurement of facilities and infrastructure in the form of 60 seedlings and planting equipment, field assistance to evaluation by percent growth, giving questionnaires before and after activities. Based on the results of the statistical tests was concluded that there was a significant difference in the ability of partners to increase due to counseling. The practice of planting 100% managed to grow well.